Analyses of Oil Contamination in the Kara Sea and Barents Sea Sediments. - Savinov, Vladimir M; Petrova, Vera I; Boitsov, Stepan; Plotitsyna, Natalia (PANGAEA, 2015)
Polycyclic aromatic hydrocarbons (PAHs) are common environmental contaminants which can be derived from anthropogenic sources, such as combustion and discharges from extraction and transport, and natural processes, including leakage and erosion of fossil carbon. Natural PAH sources contribute, along with biological activities and terrestrial run-off, to the organic carbon content in sediments.The Barents Sea region is far from many anthropogenic sources of PAH, but production and trans-shipment of hydrocarbons is increasing. We present data for polycyclic aromatic hydrocarbon (PAH) concentrations in bottom sediments from 510 stations in the Barents and White Seas, and along the northern coast of Norway.
Polyaromatic hydrocarbons in sediments from the Barents and White Seas
Keywords: Acenaphthene; Acenaphthylene; Anthracene; Area/locality; Barents; Barents Sea; Benzo(a)anthracene; Benzo(a)pyrene; Benzo(b,k)fluoranthene; Benzo(e)pyrene; Benzo(g,h,i)perylene; C1-dibenzothiophenes; C1-naphthalenes; C1-phenanthrenes; C2-dibenzothiophenes; C2-naphthalenes; C2-phenanthrenes; C3-dibenzothiophenes; C3-naphthalenes; C3-phenanthrenes; Carbon, organic, total; Chrysene; Depth, bathymetric; DEPTH, sediment/rock; Device type; Dibenzo(a,h)anthracene; Dibenzothiophene; Fluoranthene; Fluorene; Indeno(1,2,3-cd)pyrene; Laboratory; Location; Naphthalene; Nitrogen, total; Perylene; Phenanthrene; Pyrene; Reference/source; Sampling date; Size fraction < 0.063 mm, mud, pelite, silt+clay; Station label